Studi ruang rumah tinggal masyarakat Bali Katolik di Desa Canggu - Putra, Jesica Angelia; Kohdrata, Naniek; Putra, I Dewa Gede Agung Diasana (Jurnal Arsitektur Lansekap, 2020)
Study of residential space of the Catholic Bali Community at the Canggu Village. Balinese culture is a complex phenomenon based on various beliefs such as Hinduism, Shiva, Buddhism and combined with ancestral traditions therefore that Bali has a special uniqueness of the ceremonial activities performed and the architecture of the building. Over time, the many interactions that enter Bali cause interactions between communities, resulting in friction between cultures which allows acculturation to occur. One of the cultural meetings that took place in Bali was the existence of a Balinese Catholic community in Canggu Village, North Kuta District, Badung Regency, Bali. Cultural meetings that take place in this village involve Balinese Hindu culture and Catholic traditions. The purpose of this study is to study the picture of cultural encounters that occur in the pattern of Catholic Balinese residences in Canggu Village. The results obtained are that the laying of each building does not consist of one building such as a traditional Balinese house, but does not adapt to the space of the mandala, at a level that adapts the concept of the tri mandala all facing towards the main road.